Toward Successful Development Policies : Insights from Research in Development Economics - Artuc, Erhan (World Bank, Washington, DC, 2020)
What major insights have emerged from development economics in the past decade, and how do they matter for the World Bank? This challenging question was recently posed by World Bank Group President David Malpass to the staff of the Development Research Group. This paper assembles a set of 13 short, nontechnical briefing notes prepared in response to this request, summarizing a selection of major insights in development economics in the past decade. The notes synthesize evidence from recent research on how policies should be designed, implemented, and evaluated, and provide illustrations of what works and what does not in selected policy areas.